Planning budgeting process in the companies of holding type - Oserbaiuly, S.; Adambekova, G. (Journal of Economic Research & Business Administration, 2016)
A feature of the budgeting process for the holdings in terms of indus- trial and innovative development of the economy in Kazakhstan, is the co- ordination of the basic aspects of the activities of individual business units, which differ in structure and direction of economic activity, to achieve the financial results of the holding company. In general, a system of budgeting can be regarded as a specific approach to the combination of account- ing, control, analysis, management, and planning activities of the holding. The article also discussed the role and place of the budgeting system in holding structures. The classification of budgeting methods and analyzes the complexity of each stage of budgeting system in terms of innovative development of the economy.